Would you test for 5000 Shillings? HIV risk and willingness to accept HIV testing in Tanzania - Jan Ostermann; Derek S. Brown; Axel Mühlbacher; Bernard Njau; Nathan Thielman (Health Economics Review, 2015)
Objectives: Despite substantial public health efforts to increase HIV testing, testing rates have plateaued in many countries and rates of repeat testing for those with ongoing risk are low. To inform policies aimed at increasing uptake of HIV testing, we identified characteristics associated with individuals' willingness-to-accept (WTA) an HIV test in a general population sample and among two high-risk populations in Moshi, Tanzania. Methods: In total, 721 individuals, including randomly selected community members (N = 402), female barworkers (N = 135), and male Kilimanjaro mountain porters (N = 184), were asked in a double-bounded contingent valuation format if they would test for HIV in exchange for 2000, 5000 or 10,000 Shillings (approximately 1.30, 3.20, and 6.40, respectively). The study was conducted between September 2012 and February 2013. Results: More than one quarter of participants (196; 27 %) stated they would be willing to test for Tanzania Shilling (TSH) 2000, whereas one in seven (98; 13.6 %) required more than TSH 10,000. The average WTA estimate was TSH 4564 (95 % Confidence Interval: TSH 4201 to 4927). Significant variation in WTA estimates by gender, HIV risk factors and other characteristics plausibly reflects variation in individuals' valuations of benefits of and barriers to testing. WTA estimates were higher among males than females. Among males, WTA was nearly one-third lower for those who reported symptoms of HIV than those who did not. Among females, WTA estimates varied with respondents' education, own and partners' HIV testing history, and lifetime reports of transactional sex. For both genders, the most significant association was observed with respondents' perception of the accuracy of the HIV test; those believing HIV tests to be completely accurate were willing to test for approximately one third less than their counterparts. The mean WTA estimates identified in this study suggest that within the study population, incentivized universal HIV testing could potentially identify undiagnosed HIV infections at an incentive cost of 150 per prevalent infection and 1400 per incident infection, with corresponding costs per quality adjusted life year (QALY) gained of 70 for prevalent and 620 for incident HIV infections. Conclusions: The results support the value of information about the accuracy of HIV testing, and suggest that relatively modest amounts of money may be sufficient to incentivize at-risk populations to test.
Keywords: 330; HIV testing; Tanzania; Sub-Saharan Africa; Willingness to accept; Contingent valuation; Incentives